2011
DOI: 10.4236/jmp.2011.23023
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Structural and Morphological Characterization of Sr<sub>2</sub>GdRuO<sub>6</sub> Double Perovskite

Abstract: We report structural, morphological and magnetic properties of the Sr 2 GdRuO 6 compound, which is used as precursor oxide in the production process of RuSr 2 GdCu 2 O 8 superconducting ruthenocuprates. The crystalline structure was studied by X-ray diffraction and Rietveld refinement. Results reveal that material crystallizes in a monoclinic double perovskite, space group P2 1 /n (#14). Scanning Electron Microscopy experiments on samples show homogeneous granular morphology with grain size from 3 up to 7 μm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The strong contribution of 4f orbitals of the rare earth elements have a produced impact on magnetic properties. Recently the A 2 REMO 6 materials (A = Sr, Ba and Ca) with RE = rare earth and M = transition metal elements have been studied both experimentally and theoretically by addressing their crystal structure, magnetic and optical behavior [10][11][12]. It is found that, the double perovskites with Ba as A-cation adopt face-centered cubic (FCC) lattices with space group (Fm3̅ m), as shown by Ba 2 RReO 6 (R = Ho, Er) [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…The strong contribution of 4f orbitals of the rare earth elements have a produced impact on magnetic properties. Recently the A 2 REMO 6 materials (A = Sr, Ba and Ca) with RE = rare earth and M = transition metal elements have been studied both experimentally and theoretically by addressing their crystal structure, magnetic and optical behavior [10][11][12]. It is found that, the double perovskites with Ba as A-cation adopt face-centered cubic (FCC) lattices with space group (Fm3̅ m), as shown by Ba 2 RReO 6 (R = Ho, Er) [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Sr 2 GdRuO 6 double perovskite exhibits an unambiguously monoclinic structure. 94 The monoclinic 2-tilt system crystallizes with space group C2/ m and space group number 12 (PrAlO 3 ), 78 while 3-tilt systems crystallize as space group P2 1 /m with a = 5.4617(1) Å, b = 5.6545(1) Å, and c = 7.8022(3) Å (Sr 2 Ta 2 O 7 ). 90 Orthorhombic: A common distorted structure for ABX 3 perovskite-type compounds with Pbnm space group and space group number 62, with a Glazer tilt pattern a − a − c + , as observed, e.g., for, GaFeO 3 , 95 LaVO 3 , 96 or AgNbO 3 .…”
Section: Rhombohedralmentioning
confidence: 99%
“…Sr 2 Ta 2 O 7 and Sr 2 Nb 2 O 7 perovskites exhibit a distorted monoclinic structure, although controversy remains whether these natural perovskites adopt orthorhombic or monoclinic phases. The Sr 2 GdRuO 6 double perovskite exhibits an unambiguously monoclinic structure . The monoclinic 2-tilt system crystallizes with space group C2/m and space group number 12 (PrAlO 3 ), while 3-tilt systems crystallize as space group P2 1 /m with a = 5.4617(1) Å, b = 5.6545(1) Å, and c = 7.8022(3) Å (Sr 2 Ta 2 O 7 ) …”
Section: Properties Of Perovskitesmentioning
confidence: 99%
“…The material Dy 2 Bi 2 Fe 4 O 12 belongs to the family of double perovskites of type AA ′ B 2 O 6 [9,30], for which the ordering of the cations A = Dy 3+ and A ′ = Bi 3+ takes place conformally in planes and columns [31]. The lower energy distribution corresponds to independent Dy 3+ and Bi 3+ planes (figure 1(a)), which agrees with the experimental report [13], where the diffraction planes (111), ( 222), ( 131), (151), (331), (011), (101), (110), (022), ( 202) and (220) characteristic of this type of arrangement appear simultaneously.…”
Section: Cationic Orderingmentioning
confidence: 99%